The carbon isotopic signature of the upper mantle is heterogeneous - Yves Moussallam; Kenneth T. Koga; Estelle F. Rose–Koga; Cyril Aubaud; Hyun Joo Lee; Guillaume Georgeais (Communications Earth & Environment)
Abstract Knowledge of the carbon isotopic (δ13C) signature of the mantle source region of mid–ocean ridge basalts, is key to understanding carbon cycling on a planetary scale. This value has long been held at –4‰ from the study of popping rocks or –5‰ from the study of peridotitic diamonds, with little evidence of heterogeneity due to scarce direct measurements. Here we report δ13C measurements on a series of CO2–undersaturated melts inclusions from the south–west Indian mid ocean Ridge. These rare magmas never degassed CO2 hence retaining a δ13C signature in direct equilibrium to their source mantle. We found normally distributed δ13C values averaging at −7.5‰ (two standard error of ±1.4‰) and uncorrelated with major, trace and volatile element abundances nor degree of partial melting. Our data shows that the upper mantle can be heterogeneous in its carbon isotopic signature, potentially recording variable influence from subducted carbon.